Case Report: Prognostic evaluation of immunotherapy in two patients with SMARCA4-UT using TCR as a new marker - Wang, Xiayu; Zhou, Yiwei; Li, Qijiao; Wang, Jun; Qian, Yu; Yang, Bing (Frontiers in Immunology, 2025)
Thoracic SMARCA4-deficient undifferentiated tumour(SMARCA4-UT) is a newly classified subgroup of non-small cell lung cancer (NSCLC) that is rare and associated with a poor prognosis. There is a paucity of robust research regarding its treatment options and prognostic assessment. Generally, the first-line treatments for NSCLC patients with SMARCA4 are similar to those for soft tissue sarcoma (STS). STS is partially insensitive to chemotherapy and lacks specific targeted therapeutic interventions. Consequently, the immunotherapy is increasingly applied as the first-line treatment. This paper described the treatment process of two SMARCA4 patients receiving a combination of chemotherapy and immunotherapy, employing T-cell Receptor-sequencing technology(TCR). From the perspective of the immune microenvironment, we propose a novel potential marker—TCR—that may serve as an indicator for prognostic evaluation of immunotherapy in SMARCA4 patients, thereby providing a theoretical foundation from the perspectives of tissue and peripheral immunity.